The Effect of Board Gender Diversity and Firm Size on Cash Holding of Manufacturing Companies: Evidence from Indonesia - Fanny Andriani Setiawan; Herni Kurniawati (International Journal of Application on Economics and Business, 2023)
The company's cash holding is closely related to the company's efforts to minimize external funding costs. Companies that have large amounts of cash have the hope that each financing can first be financed with the company's internal funding sources, if not, then use external funding sources. The level of cash holding of a company can be influenced by various factors, including board gender diversity and firm size. This study aims to prove empirically how gender diversity in the board of directors can increase cash holding and also how company size can increase the value of cash holding. This research was assisted by the EViews 10 software program. The test results prove that gender diversity in the board of directors does not have a positive effect on cash holding, but the size of the company has a positive effect on cash holding.